Industrial viability of single-component organic solar cells - He, Yakun; Li, Ning; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Lucas, Sebastian; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Brabec, Christoph (Joule, 2022)
Although the power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing toward the 20% milestone, important factors for industrial application are mostly neglected, such as photostability and cost potential. Single-component OSCs (SCOSCs) employing materials with chemically bonded donor and acceptor moieties successfully overcome the immiscibility between the donor and the acceptor as well as the resultant self-aggregation under external stress. To inspire a broader interest, the industrial figure of merit (i-FoM) of BHJ OSCs and the corresponding SCOSCs is calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index. Despite having a slightly more complex synthesis, all SCOSCs exhibit increased i-FoM values compared with the corresponding BHJ OSCs, and with the increase in efficiency, SCOSCs possess further potential for a higher i-FoM value. With the excellent photostability of nearly all investigated single-component semiconductors, SCOSCs are coming into the focus of attention for industrial utilization.
CRIS-Team Scopus Importer:2022-07-01
Keywords: i-FoM; industrial figure of merit; PCE; photostability; power conversion efficiency; SC index; SCOSCs; single-component organic solar cells; synthetic complexity index